2005
DOI: 10.3846/16486897.2005.9636853
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation in Buildings: Situation and Dealing With Problems

Abstract: Among many artificial and natural sources of exposure the exposure which is received indoors is very important both from the point of view of its magnitude and necessity of optimization. Such sources as indoor radon and natural radionuclides in construction materials are the most significant ones. The survey results of national indoor radon show that its concentrations might be rather high in some regions. Construction materials can be a significant source of indoor radon, however, in Lithuania external exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Many studies have shown that soil is an important contributor to indoor air pollution [2]. Radon is one of these pollutants, becoming from soil, being one of the most significant sources of natural ionizing radiation [3,4], the most important sources of radon are the soil, water and building materials. Radon particles can easily infiltrate in existing houses through floor cracks, unsealed sewer pipes and many other paths [5].…”
Section: The First Section In Your Papermentioning
confidence: 99%
“…Many studies have shown that soil is an important contributor to indoor air pollution [2]. Radon is one of these pollutants, becoming from soil, being one of the most significant sources of natural ionizing radiation [3,4], the most important sources of radon are the soil, water and building materials. Radon particles can easily infiltrate in existing houses through floor cracks, unsealed sewer pipes and many other paths [5].…”
Section: The First Section In Your Papermentioning
confidence: 99%
“…A radioaktív bomlások során radioaktív (jelen esetben alfa-sugárzó) leányelemek keletkeznek, melyek a légtérben lévő parányi porszemekre, dohányfüstre ráülve bejutnak a tüdőbe, és ott megtapadva folyamatosan alfa-sugárzással bombázzák a tüdőszövetet, rákkeltő hatása van. (ABUMURAD, 2001;BUTKUS et al, 2005;ICRP 1991;ICRP 1993;KATONA et al, 2007;KÖTELES, 2007;LÁZÁR et al;SZABÓ et al, 2014b;SZERBIN et al, 1994;TÓTH, 1992;TÓTH et al, 1998;TÓTH-HÁMORI, 2005;UNSECAR, 2000) Számos kutatás foglalkozik a halálozási okok élén szereplő daganatos betegségek okainak vizsgálatával. DARBY et al (2005) szerint az Európai Bizottság által támogatott kutatásainak eredményei alapján az otthonok levegőjében található radon felelős évente körülbelül 20000 tüdőrák okozta halálesetért az Európai Unióban, ami az összes ilyen jellegű halálesetek 9%-a, illetve az összes halálos kimenetelű rákbetegségek 2%-a.…”
Section: Bevezetésunclassified
“…This is important as during the radioactive decay of radon, alfa radiation emitting daughter nuclide are created, which attach to naturally occurring dust or cigarette smoke. When this dust and smoke is inhaled, upon reaching the lungs, creates constant alfa particle bombardment of the lung tissue, thereby increasing the risk of cancer (Abumurad 2001;Butkus et al 2005;ICRP 1991ICRP , 1993Katona et al 2007;Köteles 2007;Lázár et al 2005;Szabó et al 2014aSzabó et al , 2014bSzerbin et al 1994;Tóth 1992;Tóth et al 1998;Tóth, Hámori 2005;UNSCEAR 2000).…”
Section: Introductionmentioning
confidence: 99%